2016
DOI: 10.1136/jech-2015-206475
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of risk prediction models for falls after stroke

Abstract: What this study adds?This review identifies risk prediction models for falls after stroke that require validation and impact measurement. It will facilitate future researchers in the appropriate measurement of prognostic factors for model validation, a key step in the development process of models that can be incorporated into clinical decisionmaking post stroke. 4 ABSTRACTBackground: Falls are a significant cause of morbidity after stroke. The aim of this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 42 publications
(122 reference statements)
3
24
0
2
Order By: Relevance
“…Professionals' focus on "risk" may have implications for the uptake of these interventions [36]. It must also be noted that objective "falls-risk" post stroke remains an ill-defined concept as much quantitative research has found that falls are difficult events to predict [9]. Further qualitative research could focus on how stroke survivors conceptualise the consequences of falls, and how they self-assess risk, in order to inform the development of self-management interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionals' focus on "risk" may have implications for the uptake of these interventions [36]. It must also be noted that objective "falls-risk" post stroke remains an ill-defined concept as much quantitative research has found that falls are difficult events to predict [9]. Further qualitative research could focus on how stroke survivors conceptualise the consequences of falls, and how they self-assess risk, in order to inform the development of self-management interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Fallers also demonstrate higher levels of anxiety, depressed mood and fear [6,7]. Much quantitative research has focused on the identification of modifiable risk factors for falls among this population, and the ability to predict fall events in stroke survivors returning home from hospital or rehabilitation [8,9]. Stroke survivors' own experiences of falls-risk and fall events are less well understood [10].…”
Section: Introductionmentioning
confidence: 99%
“…Of the two models derived by Mackintosh et al [9], the model including the BBS was chosen as this measure is commonly included in post-stroke studies investigating falls [6]. The model derived by Ashburn et al [11] combining two predictors was selected, as their study, with 48 events, was underpowered for the derivation of their six-item model [6,13].…”
Section: Methodsmentioning
confidence: 99%
“…As falls are complex, risk-prediction models should include more predictors [27]. The most common falls predictors entered into multi-variable models in post-stroke cohort studies are measures of neglect, gait speed, cognition, depression, falls-efficacy, the BBS and the Timed Up and Go test [6]. A derivation study with seven candidate predictors would require 70 events (an estimated sample size of approximately 400 participants based on the current study) for sufficient power to predict recurrent fall events [13].…”
Section: Future Implicationsmentioning
confidence: 99%
See 1 more Smart Citation